Effect of gold nanoparticle on structure and fluidity of lipid membrane - Mhashal, Anil R.; Roy, Sudip (Plos One, 2014)
This paper deals with the effect of different size gold nanoparticles on the fluidity of lipid membrane at different regions of the bilayer. To investigate this, we have considered significantly large bilayer leaflets and incorporated only one nanoparticle each time, which was subjected to all atomistic molecular dynamics simulations. We have observed that, lipid molecules located near to the gold nanoparticle interact directly with it, which results in deformation of lipid structure and slower dynamics of lipid molecules. However, lipid molecules far away from the interaction site of the nanoparticle get perturbed, which gives rise to increase in local ordering of the lipid domains and decrease in fluidity. The bilayer thickness and area per head group in this region also get altered. Similar trend, but with different magnitude is also observed when different size nanoparticle interact with the bilayer.

Self-assembly of phospholipids on flat supports - Mhashal, Anil R.; Roy, Sudip (Physical Chemistry Chemical Physics, 2015)
The current study deals with the self-assembly of phospholipids on flat supports using the Martini coarse grain model. We reported here the effect of the hydrophilic and hydrophobic nature of the solid supports on the lipid self-assembly. The hydrophilic and hydrophobic supports were modeled on the basis of water droplet simulations. The present work addresses the self-assembly mechanism of lipids on eight different supports with different strengths of hydrophilicity and hydrophobicity. We demonstrated how interplay between the interactions of lipid and water with the support can guide the lipid self-assembly process. Thereafter, we calculated the energetics of the components of the system to quantify the competitions between water and a lipid head-group with hydrophilic supports. Finally, the properties of the self-assembled bilayers were also analyzed and reported here.

Free energy of bare and capped gold nanoparticles permeating through a lipid bilayer - Mhashal, Anil R.; Roy, Sudip (Chemphyschem, 2016)
Herein, we study the permeation free energy of bare and octane-thiol-capped gold nanoparticles (AuNPs) translocating through a lipid membrane. To investigate this, we have pulled the bare and capped AuNPs from bulk water to the membrane interior and estimated the free energy cost. The adsorption of the bare AuNP on the bilayer surface is energetically favorable but further loading inside it requires energy. However, the estimated free-energy barrier for loading the capped AuNP into the lipid membrane is much higher compared to bare AuNP. We also demonstrate the details of the permeation process of bare and capped AuNPs. Bare AuNP induces the curvature in the lipid membrane whereas capped AuNP creates an opening in the interacting monolayer and get inserted into the membrane. The insertion of capped AuNP induces a partial unzipping of the lipid bilayer, which results in the ordering of the local lipids interacting with the nanoparticle. However, bare AuNP disrupts the lipid membrane by pushing the lipid molecules inside the membrane. We also analyze pore formation due to the insertion of capped AuNP into the membrane, which results in water molecules penetrating the hydrophobic region.

Probing the ATP-induced conformational flexibility of the PcrA helicase protein using molecular dynamics simulation - Mhashal, Anil R.; Choudhury, Chandan Kumar; Roy, Sudip (Journal of Molecular Modeling, 2016)
Helicases are enzymes that unwind double-stranded DNA (dsDNA) into its single-stranded components. It is important to understand the binding and unbinding of ATP from the active sites of helicases, as this knowledge can be used to elucidate the functionality of helicases during the unwinding of dsDNA. In this work, we investigated the unbinding of ATP and its effect on the active-site residues of the helicase PcrA using molecular dynamic simulations. To mimic the unbinding process of ATP from the active site of the helicase, we simulated the application of an external force that pulls ATP from the active site and computed the free-energy change during this process. We estimated an energy cost of similar to 85 kJ/mol for the transformation of the helicase from the ATP-bound state (1QHH) to the ATP-free state (1PJR). Unbinding led to conformational changes in the residues of the protein at the active site. Some of the residues at the ATP-binding site were significantly reoriented when the ATP was pulled. We observed a clear competition between reorientation of the residues and energy stabilization by hydrogen bonds between the ATP and active-site residues. We also checked the flexibility of the PcrA protein using a principal component analysis of domain motion. We found that the ATP-free state of the helicase is more flexible than the ATP-bound state.
Keywords: ATP; DNA helicase; PcrA; Residue reorientation; Translocation; Umbrella sampling; Unwinding